Svarga, naraka, and moksa in svargarohaṇaparva : (the perception of Hindus in Bali) - I Made Gami Sandi Untara; Farida Setyaningsih; Ni Made Sumaryani (Institute for Advanced Science Social, and Sustainable Future, 2023)
Death is not the end of life nor the limit of life; it is the gate of eternity. Only through death can immortality be achieved, and indirectly, everyone who wants to achieve immortality must first experience physical death. Life after death is related to Svarga, Naraka, and Moksa concepts. Hinduism has various texts that discuss Svarga, Naraka, and Moksa, one of which is Svargarohaṇaparva. The Svargarohaṇaparva text is the last of the eighteen parvas in the Mahābhārata tale and one of the texts dealing with svarga, Naraka, and moksa. This article is the result of a qualitative study that examines svarga, Naraka, and moksa in Svargarohaṇaparva and the perceptions of Hindus in Bali using the Hermeneutic Hans-Georg Gadamer approach. The perception of Hindus in Bali regarding svarga, Naraka, and moksa in Svargarohaṇaparva is that svarga enjoyed by people who had died when their life was always doing good; Naraka will be enjoyed by the spirit of a person who has always done bad or harmful things throughout his life; and moksha is enjoyed by limited circles, especially those who are considered holy. This is the same as what is contained in Balinese literary works, such as Geguritan Bhima Svarga, Putru Pasaji, Atma Prasangsa, Kakawin Aji Palayon, Geguritan I Japatvan, and Bagus Diarsa. However, the depiction of the atmosphere of svarga in Balinese literature shows more of the local atmosphere and Balinese traditions, such as the Meru-shaped svarga building, which is synonymous with sacred buildings in Bali. In addition, the perceptions of Hindus in Bali regarding svarga, Naraka, and moksa are also expressed in behavior, sacred buildings, and the surrounding environment, as well as religious ceremonies that reflect the concepts of svarga, Naraka, and moksa.